Contextual learning with Ethnomathematics in enhancing the problem solving based on thinking levels - Nur, Andi Saparuddin; Waluya, Stevanus Budi; Rochmad, Rochmad; Wardono, Wardono (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2020)
The differences in the development of students' thinking levels, especially in adolescence, impact the way they perceive problems. Contextual learning with ethnomathematics can provide opportunities for students to develop problem-solving abilities based on their level of thinking. This study examined the contextual learning with ethnomathematics to enhance problem-solving abilities based on thinking levels.This experimental research was conducted by posttest only control group design. The participants of this research were 60 students at a junior high school in Gowa Regency, South Sulawesi Province.Data were collected using observation sheets to determine local cultural characters that appeared at the time of treatment. The thinking level category uses the group assessment for logical thinking (GALT) test. The students' mathematical problem-solving abilities use the curved side space material to suit the local cultural context. The data analysis technique used descriptive statistics and covariance analysis (ANCOVA). This study results indicate that contextual learning with ethnomathematics influences problem-solving abilities based on the level of thinking. Furthermore, local cultural characters appear in each category of students' thinking levels. Students with formal thinking levels have better problem-solving abilities than transitional and concrete thinking levels. Contextual learning with ethnomathematics fosters problem-solving abilities based on the thinking levels.